THE DEVELOPMENT APPERCEPTION VIDEO MATERIAL OF THE PERIODICITY OF THE ELEMENT AND THE STABILITY OF THE ELEMENT GRADE X OF SMA/MA - Farikhta Nour Badriyah; I Made Sukarna (Universitas Negeri Yogyakarta, 2018)
AbstractThis research aimed to develop and know the quality of apperception video material of the periodicity of theelement and the stability of the element for first semester grade X of SMA/MA. The development model used is byadapting the ADDIE model. ADDIE model consist of 5 steps, which are Analyze, Design, Develepment,Inplementasi, and Evaluation. However, in this research did not carry out the implementation phase, so it only did4 stages. The result of this research are video based apperception that amounted to 4 videos. Based on thereviewer's assessment, the quality of the apperception video material of the periodicity of the element and thestability of the elemens for first semester grade X of SMA/MA was included in the Good category (B) with an idealpercentage of 83.1%.Keywords: Apperception, ADDIE ,research and development, video